Intrarater reliability and agreement of the physioflow bioimpedance cardiography device during rest, moderate and high-intensity exercise - Gordon, N.; Abbiss, C.; Maiorana, Andrew; Marston, K.; Peiffer, J. (UNIV ZAGREB, FAC KINESIOLOGY, 2018)
© 2018, University of Zagreb - Faculty of Kinesiology. All rights reserved. The PhysioFlow bioimpedance cardiography device provides key measures of central systolic and diastolic and peripheral vascular function. Many of these variables have not been assessed for intrarater reliability and agreement during rest, submaximal exercise and high-intensity interval exercise. Twenty healthy adults (age: 26±4 years) completed two identical trials beginning with five minutes of rest followed by two 5-minute submaximal cycling bouts at 50% and 70% of peak power output. Subjects then completed ten 30-second cycling intervals at 90% of peak power output interspersed with 60 s of passive recovery. Bioimpedance cardiography (PhysioFlow; Manatec Biomedical, France) monitored heart rate, stroke volume, cardiac output, stroke volume index, cardiac index, ventricular ejection time, contractility index, ejection fraction, left cardiac work index, end diastolic volume, early diastolic filling ratio, systemic vascular resistance and systemic vascular resistance index continuously throughout both trials. Intraclass correlation coefficients (ICC), standard errors of measurement and minimal detectable differences were calculated for all variables. Heart rate, stroke volume, cardiac output, left cardiac work index and end diastolic volume demonstrated a good level of reliability (ICC>.75) at rest, during submaximal exercise and high-intensity interval exercise. All other variables demonstrated inconsistent reliability across activity types and intensities. When using the PhysioFlow device, heart rate, stroke volume, cardiac output, left cardiac work index and end diastolic volume were deemed acceptable for use regardless of exercise type (continuous vs. interval) or intensity (low, moderate, or high). However, other variables measured by this device appear less reliable.